(untitled) (PANGEEA, 2025)
Bucium is a commune in Alba County, located in the, occupying third of north-west of the county. Apuseni Mountains include 25 communes and 4 small cities. In analyzing how specific types of evolutionary and population for the last 160 years, we can see that the community is within the common demographic entire area in which I see certain stages of population growth caused by several factors, but much more obvious and visible is depopulation and population decline in Bucium, especially after 1945, as the entire area of the Apuseni Mountains.